2022
DOI: 10.3389/fimmu.2022.951529
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic stratification based on m5C regulators acts as a novel biomarker for immunotherapy in hepatocellular carcinoma

Abstract: BackgroundImmunotherapy is a promising anti-cancer strategy in hepatocellular carcinoma (HCC). However, a limited number of patients can benefit from it. There are currently no reliable biomarkers available to find the potential beneficiaries. Methylcytosine (m5C) is crucial in HCC, but its role in forecasting clinical responses to immunotherapy has not been fully clarified.MethodsIn this study, we analyzed 371 HCC patients from The Cancer Genome Atlas (TCGA) database and investigated the expression of 18 m5C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Aberrant m 5 C modifications of RNA have been reported to be closely associated with tumorigenesis and immune infiltration across various cancer types, rendering them promising targets for anticancer therapy. Recently, prognostic models based on m 5 C-associated genes have emerged for HCC, offering novel insights into the role of this RNA modification in cancer development [ 22 26 ]. A previous study revealed that elevated NSUN5 expression promotes both in vitro HCC cell proliferation and migration as well as in vivo HCC tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant m 5 C modifications of RNA have been reported to be closely associated with tumorigenesis and immune infiltration across various cancer types, rendering them promising targets for anticancer therapy. Recently, prognostic models based on m 5 C-associated genes have emerged for HCC, offering novel insights into the role of this RNA modification in cancer development [ 22 26 ]. A previous study revealed that elevated NSUN5 expression promotes both in vitro HCC cell proliferation and migration as well as in vivo HCC tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have partially explored the prognostic significance of m6A modification in BRCA and CHOL (Feng et al 2022c ; Wei et al 2023 ). Furthermore, m5C can serve as a potential biomarker for predicting the efficacy of LIHC immunotherapy (Liu et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%